(3SjQ CYdGe GdfHdGAs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3GdeLfhf bjS Hf GdedhM (B_ (3hbjd GHf eYGP , hbjd ESeg HMJQi Hf GdLYO , hbjd ZjQ Pdc ef Hfi YGeQ Hf UYUYg , hbjd ef Hfi cYH s
(3BNQgG (B:s
(3WhjS GdeOfi CMO ef jVQH Hg GdeKd ai UfGYI GdZfGA CSeg YHO GdefYe YjSi Hf YHO Gddg haWe jhe ehJ Ydi QVi Gddg Yfge eGJ SfI EKfjf hJSYjf s
(3bGe HJMbjbg O (B/ (3UdGM GdOjf GdefLOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1015s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs